Nuclear Expression of GS28 Protein: A Novel Biomarker that Predicts Worse Prognosis in Cervical Cancers. - Uiju Cho; Hae-Mi Kim; Hong Sik Park; Oh-Joo Kwon; Ahwon Lee; Seong-Whan Jeong (PLoS ONE, 2016)
The protein GS28 (28-kDa Golgi SNARE protein) has been described as a SNARE (Soluble N-ethylmaleimide-sensitive factor attachment protein receptors) protein family member that plays a critical role in mammalian ER-Golgi or intra-Golgi vesicle transport. Little is known about the possible roles of GS28 in pathological conditions. The purpose of this study was to evaluate GS28 expression in cervical cancer tissues and explore its correlation with clinicopathological features and prognosis.We investigated GS28 expression in 177 cervical cancer tissues by using immunohistochemistry and evaluated the correlation of GS28 expression with clinicopathological features, the expression of p53 and Bcl-2, and prognosis of cervical cancer patients. Immunoblotting was performed using six freshly frozen cervical cancer tissues to confirm the subcellular localization of GS28.Immunoreactivity of GS28 was observed in both nuclear and cytoplasmic compartments of cervical cancer cells. High nuclear expression of GS28 was associated with advanced tumor stages (P = 0.036) and negative expression of p53 (P = 0.036). In multivariate analyses, patients with high nuclear expression of GS28 showed significantly worse overall survival (OS) (hazard ratio = 3.785, P = 0.003) and progression-free survival (PFS) (hazard ratio = 3.019, P = 0.008), compared to those with low or no nuclear expression. It was also a reliable, independent prognostic marker in subgroups of patients with early stage T1 and negative lymph node metastasis in OS (P = 0.008 and 0.019, respectively). The nuclear expression of GS28 was confirmed by immunoblotting.High nuclear expression of GS28 is associated with poor prognosis in early-stage cervical cancer patients. GS28 might be a novel prognostic marker and a potential therapeutic target in cervical cancer treatment.